Implentasi Aplikasi Ujian Online Berbasis Client Server Studi Kasus di SMA Negeri 3 Selong - Suhartini Suhartini; Muhammad Saiful; Yahya Yahya; Nurhidayati Nurhidayati (Infotek: Jurnal Informatika dan Teknologi, 2022)
Exams based on the Big Indonesian Dictionary can mean something that is used to test the quality of something (intelligence, ability, learning outcomes, etc.). In addition to being carried out in writing and orally, the exam can also be carried out using computer aids. The purpose of the examination is aimed at assessing the achievement of graduate competency standards for all subjects. Exams are carried out according to the curriculum used by the education unit, and can be carried out in even and/or odd semesters by each education unit. If the exam using a computer is carried out in a computer network, be it an intranet or the internet, it can be categorized as an online exam. In the form of the research method used is in the form of engineering research which in preparation is carried out in the form of a plan, design, or the results of the development of a system or product model. In the research, the process of software engineering for online exam applications based on client server was carried out. The outputs of this research are needs analysis, application design and implementation in the online exam.